1998
DOI: 10.1097/00004424-199808000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes of the Spinal Canal in Patients With Cervical Spondylosis at Flexion and Extension Using Magnetic Resonance Imaging

Abstract: Magnetic resonance imaging identified a significant percentage of increased spinal stenosis at flexion and, especially, at extension, which was not observed at neutral position (0 degree). Flexion and extension MR imaging demonstrates additional information using a noninvasive technique concerning the dynamic factors in the pathogenesis of cervical spondylotic myelopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 17 publications
1
65
0
1
Order By: Relevance
“…Many techniques have been described to quantify the degree of narrowing of the subarachnoid space, or compromise of the spinal cord or exiting roots [25][26][27][28][29][30]. It is clear that no simple reliable technique exists and radiologists seem to be very poor at reliably assessing the degree of cord compression.…”
Section: Discussionmentioning
confidence: 99%
“…Many techniques have been described to quantify the degree of narrowing of the subarachnoid space, or compromise of the spinal cord or exiting roots [25][26][27][28][29][30]. It is clear that no simple reliable technique exists and radiologists seem to be very poor at reliably assessing the degree of cord compression.…”
Section: Discussionmentioning
confidence: 99%
“…The body of the superior vertebra slides posteriorly on its inferior neighbor only when the cervical spine is extended. The relationship between these 2 vertebrae is [13][14][15] demonstrated that in healthy individuals, compared with its size in the neutral and flexed positions the cervical subarachnoid space was smallest during cervical spine extension. In patients with increasing stages of degenerative disease of the cervical spine, Muhle et al observed an increasing prevalence of functional cord impingement from the posterior aspect and from the anterior and posterior aspects (pincer effect) during cervical spine extension.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,[12][13][14][15] Magnetic resonance im aging is the preferred radiological tool for diagnosing CSM because it not only anatomically depicts how the spinal cord is compressed but also reveals pathological changes in the spinal cord. However, it is difficult to make objective clinical assessments of CSM on the basis of radiological findings alone.…”
mentioning
confidence: 99%
“…Disc degeneration was noted in 60% of those over the age of 40 [40]. Muhle et al [41] have shown that significant increase of spinal stenosis have been observed in extension more so than in flexion. Dynamic MRI studies have shown that patients with a congenitally narrow spinal canal [<13mm] predispose to the development of radiographic dynamic cord compression and potentially clinical myelopathy [42].…”
Section: Radiological Evidence Of Impact Of Posterior Osteophytementioning
confidence: 96%